Pengaruh Pemberian Daun Sengon (Albizzia falcataria) Hasil Rendaman dengan Larutan Ca(OH)2 Terhadap Bobot Karkas dan Bobot Organ Pencernaan Ayam Pedaging - Akmal, Akmal (Fakultas Peternakan Universitas Jambi, 2008)
This research aims at meauring the use of Sengon soaked in kapur tohor and is effect on the performance of broiler. The Study used 100 broiler Hubber aged 3 days and 5 treatments ration which contain different sengon. The design used in this study was completely randomized design (CRD) with 5 treatmen. Parameter measured were ration consumption, carcas, and digestive tract. The result of this study shows that the use of sengon in the ration is effective segnificantly (P<0,05) on the ration consumtion, carcass, and digestive tract. It could be concluded that sengon can be used up to 7,5% in the ration of the broiler.